Impact of the COVID-19 pandemic on some modifiable risk factors of dementia in an aging, rural Indian population - Sundarakumar, Jonas S.; Mensegere, Abhishek L.; Malo, Palash K.; Ravindranath, Vijayalakshmi; , on behalf of SANSCOG Collaborators (Frontiers in Psychiatry, 2023)
Introduction: The impact of the COVID-19 pandemic and associated lockdowns is likely to have caused adverse changes in lifestyle-related / cardiovascular risk factors and other such modifiable risk factors of dementia. We aimed to examine the pandemic's impact on some modifiable risk factors of dementia among rural Indians belonging to a large, prospective aging cohort – Srinivaspura Aging, NeuoSenescence, and COGnition (SANSCOG). Methods: This was a cross-sectional study among adults aged ≥ 45 years (n= 3148; 1492 males & 1656 females) residing in the villages of Srinivaspura in Karnataka state, India. SANSCOG study data (clinical and biochemical assessments) of these participants were obtained from three distinct periods: (i) the "pre-COVID period" – before India's nationwide lockdown on 24 March 2020, (ii) the "COVID period" – during the first and second waves of the pandemic, wherein the social restrictions were prominent (25 March 2020 to 30 September 2021), and (iii) the "post-COVID period" – after easing of restrictions eased (from 1 October 2021 onwards). Proportions of participants with diabetes, hypertension, obesity, dyslipidemia (diagnosed using standard criteria), and depression (diagnosed using the Geriatric Depression Scale) were compared between the above three periods. Results: The odds of having obesity, abnormal triglycerides, and depression among individuals in the COVID period were 1.42 times, 1.38 times, and 2.65 times more than the odds in the pre-COVID period, respectively. The odds of having hypertension, obesity, abnormal total cholesterol, abnormal triglycerides, abnormal LDL, and depression among individuals in the post-COVID period were 1.27 times, 1.32 times, 1.58 times, 1.95, 1.23 and 3.05 times more than the odds in the pre-COVID period, respectively. The odds of diabetes did not differ between any of the three periods. Discussion: We found significantly higher odds of some of the studied risk factors in the COVID and post-COVID periods compared to the pre-COVID period, suggesting that the pandemic adversely impacted the physical and psychological health of this marginalized, rural Indian population. We call for urgent public health measures, such as multimodal, lifestyle-based, and psychosocial interventions, to mitigate this negative impact and reduce the future risk of dementia.